অপারেশন ভারতীয় হাইকমিশন - আহমদ, মহিউদ্দিন (ঢাকা : প্রথমা প্রকাশন, 2021)
Articles on the attack on Indian Embassy at Dhaka on 26th November 1975, conspired by Jātīẏa Samājatāntrika Dala (Bangladesh)
গ্রন্থপঞ্জিগত নির্দেশিকা অন্তর্ভুক্ত।
Donated By Akbar Ali Khan
In Bengali.
Keywords: India -- Politics and government